2016
DOI: 10.3847/0004-637x/823/2/153
|View full text |Cite
|
Sign up to set email alerts
|

ON THE STATE OF A SOLAR ACTIVE REGION BEFORE FLARES AND CMEs

Abstract: Several attempts have been made to find reliable diagnostic tools to determine the state prior to flares and related coronal mass ejections (CMEs) in solar active regions (ARs). Characterization of the level of mixed states is carried out using the Debrecen sunspot Data for 116 flaring ARs. Conditional flare probabilities (CFPs) are calculated for different flaring classes. The association with slow/fast CMEs is examined. Two precursor parameters are introduced: (i) the sum of the (daily averaged) horizontal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…The sum of the horizontal magnetic field gradient (Korsós and Erdélyi, 2016), G S , is given by the formula:…”
Section: Sum Of the Horizontal Magnetic Field Gradientmentioning
confidence: 99%
“…The sum of the horizontal magnetic field gradient (Korsós and Erdélyi, 2016), G S , is given by the formula:…”
Section: Sum Of the Horizontal Magnetic Field Gradientmentioning
confidence: 99%
“…The S l−f and G S can be determined from the moment of first available observation of sunspot groups, because the applied umbrae data are suitably corrected for geometrical foreshortening in the SOHO/MDI-Debrecen Data (SDD 3, ) and the SDO/HMI-Debrecen Data (HMIDD 4 ) catalogues (Baranyi et al, 2016). Furthermore, these two morphological parameters were shown to be potential indicators for upcoming flares on a smaller number of typical test cases (Korsós and Erdélyi, 2016). The test cases included 116 ARs, which were selected from SDD.…”
Section: Two Morphological Parametersmentioning
confidence: 99%
“…Furthermore, Kontogiannis et al (2018) investigated and tested some of those parameters, which were identified as efficient flare predictors. These parameters include, e.g.,, a quantity denoted as B eff that measures the coronal magnetic connectivity between the opposite magnetic field elements (Georgoulis and Rust, 2007), Ising energy E Ising of a distribution of interacting magnetic elements (Ahmed et al, 2010), the sum of the horizontal magnetic field gradient G S (Korsós and Erdélyi, 2016), and the total unsigned nonneutralized currents, I NN,tot (Kontogiannis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing flare and CME forecasting tools are usually based on the local dynamics of active regions, such as the magnetic topology (e.g., Korsós et al 2014, Korsós & Erdélyi 2016. However, certain global phenomena are also able to provide opportunities for predicting the locus of solar eruptive events, such as the longitudinal inhomogeneous properties of active regions (e.g., Bumba et al 1965;Bogart 1982;Berdyugina et al 2006;Balthasar 2007;Zhang et al 2011).…”
Section: Motivationmentioning
confidence: 99%